Clinical profile and outcome of traumatic brain injury in children: record-based descriptive study - Rathod, Lekha Bhupendra; Shidam, Umakant G.; Kesaria, Ruchir; Mohata, Sanket; Lakhe, Prashant; Prabhudesai, Sanket; Jha, Mala (International Journal Of Community Medicine And Public Health, 2021)
Background: Paediatric head injury is considered to be a major public health problem and is often associated with significant morbidity and mortality in severe cases. The present study aimed to explore the demographics, mechanism of injury and clinical aspects of injury in children in a peripheral hospital attached to tertiary care centre. Methods: Electronic medical records of all paediatric patients aged ≤12 years with traumatic brain injury admitted during one-year period from January to December 2018 were reviewed. Epidemiological and clinical data of paediatric patients with traumatic brain injury (TBI) were analysed using SPSS version 20. Results: The medical records of 203 paediatric patients with TBI were analysed. The majority of the injury occurred in patients belonging to age-group 1-6 years. The number of male children outnumbered (58.1%) that of female children (41.9%). Fall from height was the most common mode of injury, followed by fall from a staircase. As per the Glasgow coma scale, 4% patients had severe head injury. Vomiting and headache was the most common symptom at admission (50.2%), a subdural hematoma was the most common lesion seen on computed tomography scans; frontal bone was the most common site of skull bone injury. Cutaneous injuries associated with contused lacerated wounds were the most common external injuries, 92.1% completely recovered with conservative management. Conclusions: Increasing incidence of paediatric trauma suggests the need for supervision during play and identification of environmental risk factors for such injuries. Parental advice and supervision is recommended to prevent accidental falls.